SERVICES OFFERED BY THE RBKS AND TRAINING NEEDS OF VILLAGE AGRICULTURAL ASSISTANTS IN GUNTUR DISTRICT - O.SARADA*, G.V. SUNEEL KUMAR; G. SIVANARAYANA (The Journal of Research ANGRAU, 2023)
The attempt was made to analyse the awareness and utility of RBK services by the farmers and training needs of Village Agricultural Assistants (VAAs) in Guntur district. Hundred farmers from 10 subdivisions and 165 VAAs from 55 mandals were selected asthe respondents. Majority of the farmers were aware of distribution of quality fertilizers (88.00%), e-crop booking (86.00%), soil & water testing facility (78.00%), free crop insurance/ animal insurance (75.00%), provision of quality seed (green manure/ crop seed/fodder seed/concentrate feed) (73.00%), distribution of quality pesticides (60.00%) and provision of need based information to farmers on crop healthmanagement (57.00%). With respect to utility, only few services are utilised by the farmers’ viz., e crop booking (82.00%), free crop insurance / animal insurance (59.00%) and distribution of quality fertilizers (58.00%). Majority of the Village Agricultural Assistants expressed that Integrated Disease Management (87.27 TNI & Rank I), Integrated Pest management (83.64TNI &Rank II), new varieties (81.41TNI & Rank III),Micro nutrient management (80.80TNI & Rank IV), Integrated weed management (80.20 TNI & Rank V) are the major areas of training needed by them. Major constraints expressed by VAAs are inability to meet the demands of farmers with respect to providing all of them with subsidies, inability to maintain sufficient fertilizers, pesticides and other stocks as required by farmers and Heavy work load.